2016
DOI: 10.31703/glr.2016(i-i).08
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of CLT in the ESL Context of Pakistan

Abstract: The study investigates the effectiveness of Communicative Language Teaching (CLT) in Public sector colleges of Pakistan. The experimental study traces improvement in comprehension and writing skills of intermediate level students (studying in grades 11 and 12). An experiment group and a control group are used to study the effects of CLT on learners’ progress. A pre-test and post-test are carried out to measure any improvement in the students’ cognitive learning process. The experiment group is given treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…2. The concentration effect of fillers on viscosity is also observed in other natural rubber-based pressure-sensitive adhesives [9][10][11].…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…2. The concentration effect of fillers on viscosity is also observed in other natural rubber-based pressure-sensitive adhesives [9][10][11].…”
Section: Resultsmentioning
confidence: 91%
“…It was found that the single-lap shear joint strength improved significantly with the addition of 10 wt% loading of Al 2 O 3 , Al, and Cu particles in the epoxy adhesive. Recently, we also carried out a few studies on the adhesion properties of filled natural rubber adhesives [9][10][11]. Results indicate that maximum adhesion property is observed at an optimum filler loading.…”
Section: Introductionmentioning
confidence: 99%
“…The Ge crystal adopts a typical diamond‐structure. Note that GeS and GeSe possess typical layered structure, where chemically bonded Ge–S zigzag‐type layers are stacked by vander Waals forces, which are considered as very beneficial to ion intercalation and suitable for use in energy storage . The representative SEM images of Ge@C, GeS@C and GeSe@C composites are shown in Figure b, Figure b and Figure b.…”
Section: Resultsmentioning
confidence: 99%
“…Group 14 chalcogenides are considered as highly promising materials for technical application in thermoelectric generators, optoelectronic devices, temperature sensors, telecommunication, holographic recording systems, and in memory relays . Thermoelectric (TE) materials have received growing interest during the last years since they allow the conversion of waste heat into renewable energy (Seebeck effect), whereas the opposite Peltier effect is used for cooling devices.…”
Section: Introductionmentioning
confidence: 99%
“…Effective thermoelectric materials require therefore good electrical transport properties and high Seebeck coefficients, whereas their thermal conductivity should be as low as possible. The higher the ZT value, the higher is the TE conversion efficiency and a ZT value of at least 1 is necessary , …”
Section: Introductionmentioning
confidence: 99%